PENGARUH TRICHODHERMA sp. TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON var Honey Orange DI GREENHOUSE UNISBA - Serdani, Army Dita; Palupi Puspitorini; Tri Endrawati; Eko Siswanto; Budiman, Eko Wahyu (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2025)
Melon (Cucumis melo L.) Honey Orange variety is a horticultural commodity with superior taste, aroma, and nutritional content, but its productivity is relatively low. The purpose of this study was to examine the effect of various doses of Trichoderma sp. on the growth and yield of melon plants of the Honey Orange variety. The study used a Randomized Block Design (RBD) with six treatments, namely T0 = without Trichoderma sp., T1 = 5 g/L, T2 = 10 g/L, T3 = 15 g/L, T4 = 20 g/L, and T5 = 25 g/L. The parameters observed were the number of leaves (leaflets), stem diameter (cm), fruit diameter (cm), and fruit weight (g). The data obtained were analyzed using analysis of variance, followed by Duncan's Test at the 5% level. The results of this study showed that the administration of Trichoderma sp. had a significant effect on all observed growth and yield parameters. The T3 treatment (15 g/L) was the most effective treatment, with an increase in the number of leaves and stem diameter, and produced the highest fruit diameter and fruit weight, namely 36.48 cm and 876 g, respectively. Thus, the application of Trichoderma sp. at a dose of 15 g/L can be recommended as the optimum dose to increase the growth and productivity of the Honey Orange melon variety.